The Role of Young Entrepreneurs in Increasing Family Income in North Sinjai District - Adriani; Reza Wardiansyah; Awaluddin; Satria Ramli (IECON: International Economics and Business Conference, 2024)
This article explores the contributions of young business owners in North Sinjai District to improving family income. The study focuses on identifying the role of young entrepreneurs in enhancing their family's economic conditions. Three young entrepreneurs running businesses in North Sinjai District were selected as subjects for this qualitative and naturalistic research. Data were collected through interviews and documentation. The research findings reveal that, despite facing competition from established businesses, young entrepreneurs with creativity, innovation, and entrepreneurial attitudes significantly contribute to increasing family income. These young business owners are able to leverage their fresh perspectives and adaptive strategies to create competitive businesses that meet local needs. Field observations further indicate that many young people in North Sinjai District are actively involved in various sectors, both in goods and services, showcasing their entrepreneurial spirit. The study emphasizes that the involvement of young entrepreneurs not only alleviates the financial burden on their families but also creates new income opportunities. Their efforts help diversify the local economy and provide valuable support to their households. The findings highlight the importance of fostering entrepreneurship among youth, as it can lead to greater financial independence and contribute to broader economic growth in the region. Future research could investigate the impact of mentorship programs or government support in nurturing young entrepreneurship.